A case report of late-onset central toxic keratopathy following femtosecond laser-assisted in situ keratomileus - Xiaoting Xiao; Xin Li; Liangding Zheng (BMC Ophthalmology)
Abstract Background CTK is a rare, acute, noninflammatory, self-limiting corneal condition that occurs after refractive surgery and is characterized by dense central stromal opacification. Clinical hallmarks include significant central corneal haze, stromal thinning, Descemet’s membrane folds, and a significant hyperopic shift within 3–9 days postoperatively. We reported a case of CTK occurring 5 years after refractive surgery. Case report A myopic patient who underwent Femtosecond Laser-Assisted In Situ Keratomileusis (FS-LASIK) five years prior presented with pain and blurred vision after rubbing his right eye. Initially, diagnosed with Stage III diffuse lamellar keratitis (DLK), the patient was treated with topical corticosteroids (prednisolone acetate and fluorometholone), antibiotics (tobramycin), intravenous vitamin C, and corneal lesion debridement. After treatment, the patient’s vision improved. The diagnosis was later revised to corneal toxic keratopathy (CTK). Conclusions Early and correct differentiation between CTK and DLK could lead to a good prognosis. Corneal confocal microscopy is helpful in diagnosis. A reduction in the use of corticosteroids and antibiotics led to further ocular amelioration. Moreover, this treatment should actively promote corneal epithelial repair, and in the future, the use of vitamin C in the early stage of the disease can be considered.